A supramolecular assembly mediated by host–guest interactions for improved chemo–photodynamic combination therapy. Issue 30 (13th March 2020) - Mao, Weipeng; Liao, Yujun; Ma, Da
Abstract : A supramolecular nanomedicine for improved chemo–photodynamic therapy. Abstract : We report a supramolecular nanomedicine (SNM-3) based on a camptothecin–tetraphenyl porphyrin conjugate, camptothecin–polyethylene glycol conjugate, and acyclic cucurbit[ n ]uril. The supramolecular nanomedicine is tunable by varying the composition of the three components to optimize the nanoscale morphology and therapeutic efficacy. The optimized supramolecular nanomedicine possesses great stability and enhanced intracellular singlet oxygen generation efficiency. Cytotoxicity assay demonstrates that SNM-3 improves the efficacy of chemo–photodynamic combination therapy against three cancer cell lines.